A Study of Redundancy and Neutrality in Evolutionary Optimization - Correia, Marisol B. (2015)
Some authors consider that evolutionary search may be positively influenced by the use of redundant representations, whereas others note that the addition of random redundancy to a representation could be useless in optimization. Given this lack of consensus, two new families of redundant binary representations are developed in this paper.